Body Sensors and Electrocardiography - Trobec, Roman; Tomašić, Ivan.; Rashkovska, Aleksandra; Depolli, Matjaž; Avbelj, Viktor; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This monograph presents a comprehensive overview of the electrocardiography from the aspect of wireless and mobile monitoring and its potential for personalized health management. The topical focus is on the implementation and efficient application of user friendly m-Health systems. The target audience comprises biomedical engineers, medical doctors, students, industrial experts and health managers developing m-Health solutions.
Introduction -- From multichannel ECG to wireless body sensors -- Software for an mHealth system -- ECG pilot studies -- Lead theory of differential leads and synthesis of the standard 12-lead ECG -- Commercial ECG systems -- Final remarks and conclusions.
Keywords: Biomedical engineering; Medical informatics; Cardiology; Signal processing; Biomedical Engineering and Bioengineering; Health Informatics; Cardiology; Signal, Speech and Image Processing